A CREB1 Gene Polymorphism (rs2253206) Is Associated with Prospective Memory in a Healthy Cohort - Avgan, Nesli; Sutherland, Heidi G.; Lea, Rodney A.; Spriggens, Lauren K.; Haupt, Larisa M.; Shum, David H. K.; Griffiths, Lyn R. (Frontiers in Behavioral Neuroscience, 2017)
Prospect memory (PM) is generally defined as remembering to perform intended actions in the future and is important for functioning in daily life. Cyclic adenosine monophosphate (cAMP) responsive element binding protein 1 (CREB1) plays an important role in cognitive functions. In this study, we hypothesized that genetic variation in the CREB1 gene is associated with PM. We genotyped a CREB1 promoter polymorphism rs2253206 and tested it for association with PM in 619 healthy subjects. PM performance was measured using the Prospective and Retrospective Memory Questionnaire (PRMQ), the Comprehensive Assessment of Prospective Memory (CAPM), and the Memory for Intentions Screening Test (MIST). Generalized linear model analysis was conducted for each PM test independently using different inheritance models to identify any associations (p<0.05). After multiple testing adjustments, a significant association was found between the rs2253206 genotype and PM performance for CAPM instrumental activities of daily living measure (p=0.016). These results suggest that the rs2253206 polymorphism in the CREB1 gene locus is associated with PM in healthy individuals and contributes to knowledge on the genetics of this particular type of memory.